2005
DOI: 10.1370/afm.303
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Practice-Based Research Networks: Working at the Interface Between Research and Quality Improvement

Abstract: PBRNs appear to be evolving from clinical laboratories into learning communities, proving grounds for generalizable solutions to clinical problems, and engines for improvement of primary care delivery systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
204
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(213 citation statements)
references
References 56 publications
3
204
0
6
Order By: Relevance
“…[19][20][21][22] Research networks that design feasible, clinically relevant studies may be more likely to succeed in recruiting physicians. 20,23 Appealing studies should combine minimal burden with real-time improvements to patient care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22] Research networks that design feasible, clinically relevant studies may be more likely to succeed in recruiting physicians. 20,23 Appealing studies should combine minimal burden with real-time improvements to patient care.…”
Section: Discussionmentioning
confidence: 99%
“…20,23 Appealing studies should combine minimal burden with real-time improvements to patient care. 21,22 One way to accomplish this is to merge traditional research methods with QI initiatives. 19,21,22 The addition of QI activities meeting standards for MOC Part 4 Credit increases the valueofa researchprojectin 2 ways: (1) it trains practitioners in a clinically valuable skill (QI), and (2) it providespediatricianswithanopportunity to earn credit hours toward board certification.…”
Section: Discussionmentioning
confidence: 99%
“…We then assembled a clinician expert advisory group by recruiting clinicians who were part of the Dartmouth Primary Care Cooperative Research Network (CO-OP), one of the oldest primary care research networks in the United States. 43 Fifteen community-based clinicians representing primary care and cardiology agreed to participate in either an in-person or a web-based small group interview moderated by the study project coordinator (LJ). The semistructured interview guide explored clinicians' personal definition of ''palliative care;'' characteristics of HF patients appropriate for PC; clinicians' approach to advanced stage (versus early stage) HF patients; PC referral triggers; and feedback regarding the proposed intervention design, materials, and outcome measures.…”
Section: Methodsmentioning
confidence: 99%
“…The themes that arose from the literature indicated that PBRNs serve a variety of objectives and can be developed using frameworks such as knowledge translation ((Armstrong and Kendall 2010;Tapp and Dulin 2010), quality assurance (Mold and Peterson 2005;Brouwer et al 2006), research capacity building (Del Mar and Askew 2004;Green et al 2005) and CoPs (Wenger et al 2002;Agrawal and Joshi 2011). The literature suggested that the evolution of CoPs can be intentionally fostered if appropriate seeding conditions are present (Agrawal and Joshi 2011).…”
Section: Establishing the Illawarra And Southern Practice Research Nementioning
confidence: 99%
“…Comparably, practicebased research networks (PBRNs) are collaborative learning communities that identify, disseminate and integrate new knowledge to improve primary care processes and patient outcomes (Mold and Peterson 2005). When PBRNs are constructed to facilitate non-hierarchical relationships based on trust and co-operation (Griffiths et al 2000), they reflect the components of a community of practice.…”
Section: Introductionmentioning
confidence: 99%